Pengaruh Penerapan Model Problem Based Learning Terhadap Hasil Belajar Subtema Sumber Energi - Rafika Putri Aji; Wawan Syahiril Anwar; Rukmini Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the effect of the Problem Based Learning model on the learning outcomes of data presentation. The approach used is a quasi-experimental with two groups at the State Elementary School Tunggilis. The subjects of this study were students in class IVA and IVB, which consisted of 72 students. This research was conducted in the even semester of the 2022/2023 academic year. The result of this study indicates that there is an effect of using the problem based learning model on the learning outcomes in data Presentation material. This can be seen from the N-Gain value in the experimental class group of 63,04, while for the control class group the N-Gain value is 55,98. The completeness of learning outcomes obtained by the experimental class group is 78% while in the control class it is 63%. And the results of hypothesis testing show that Ho is rejected and Ha is accepted, because tcount (3,01709) > ttabel (1,99444). With this it can be concluded that the research has a better and significant effect.Â